Can inoculation with diazotrophic bacteria decrease the productivity loss of defoliated Vigna unguiculata (L.) Walp? - Caliane da S. Braulio; Leonardo F. L. da Silva; Claudemir S. da Silva; Andreza de J. Correia; Juan M. A. Rocabado; Rafaela S. A. Nóbrega (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The objective of this study was to evaluate the effect of artificial defoliation on vegetative and productive stages of cowpea inoculated with diazotrophic bacteria, in two experiments. The first experiment was performed in a greenhouse with 5 × 5 factorial (five defoliation percentages and five N sources), with four repetitions. N sources consisted of bacterial inoculation with strains INPA 03-11B, UFLA 03-84, UFRB FA34C2-2, and two control treatments: i - with N fertilization and ii - blank control, without N fertilization and without inoculation. The second experiment was performed in the field, in a 3 × 5 factorial scheme, with three repetitions. Treatments consisted of three N sources: with N fertilization, with bacterial strain INPA 03-11B that was selected in the first experiment, and five percentages of artificial defoliation. Defoliation percentages for both experiments were 0, 25, 50, 75, and 100%. Artificial defoliation during the vegetative stage caused reduction in the dry mass of bacterial nodules. Inoculation increased plant tolerance to defoliation and enhanced grain nutrient concentration (N and P). Inoculation with the strain INPA 03-11B allowed cowpea plants to tolerate 50% defoliation in the vegetative stage. The mean productivity of cowpea was reduced under > 50% defoliation during the productive stage; therefore, control of defoliating pests until the productive stage is not necessary under field conditions.